Mayo Clinic guide to fibromyalgia - Abril, Andy; Bruce, Barbara K. (Mayo Clinic Press, 2019)
Drawing on decades of experience in treating fibromyalgia, Mayo Clinic Guide to Fibromyalgia offers research-supported, practical strategies that can help anyone with fibromyalgia live their best life now. From personal stories of people living with fibromyalgia to the compassionate expertise of its medical editors, this book seeks to first connect with people who have fibromyalgia in a way that they may not have experienced from loved ones and even doctors. From there, readers will learn about what fibromyalgia is <U+2013> and isn<U+2019>t <U+2013> and find solace in knowing that they<U+2019>re not alone in the challenges that they face. The half of the book sets the foundation for the second half, which outlines practical strategies shown to be effective in managing fibromyalgia. Along the way, worksheets will help guide readers toward finding the best mix of strategies for managing their symptoms. The entire book comes together in the last part, where readers will put everything they<U+2019>ve learned into an actionable daily plan that they can start using right away.